Are maldanids from deep-sea reduced habitats closely related? Implications of a new wood-fall species of Nicomache from the South China Sea - Wang, Yueyun; Zhou, Yadong; Zhang, Dongsheng; Wang, Chunsheng (Frontiers in Marine Science, 2024)
A new wood-fall-associated maldanid discovered at a depth of 2,321 m in the South China Sea is here morphologically and molecularly described as Nicomache tigilli sp. nov. The new species is characterized as having 21 chaetigers, a prostomium rounded anterior, an arched cephalic keel, anterior ends of nuchal grooves curved outwards, 3–6 acicular spines on chaetigers 1–3, notopodia with simply long and narrow capillary chaetae, and an anal funnel with triangular, unequal-sized anal cirri. Our molecular analyses of the genus Nicomache, encompassing COI, 16S, 18S, and 28S genes support establishing the new species, which appear phylogenetically closely related to the other species of the genus from reduced habitats.